Emerging Issues in Prison Health - Elger, Bernice S.; Ritter, Catherine; Stöver, Heino (Springer Netherlands : Imprint: Springer, 2017)
This volume recognizes and addresses the health care issues of prisoners, to establish best practices and to learn about approaches to these challenges from around the world. It presents new evidence on several emerging and classical prison health issues. The first goal of this volume is to address emerging issues related to health in prison. Second, it presents the most recent research-based evidence and translates it to the practice. The third goal, is that it allows for sufficient diversity while also incorporating updates of some important already recognized prison health. The volume discusses prisons and the life and well-being of prisoners and staff, after growing problems as drug misuse (incl. tobacco smoking), infectious diseases (HIV/AIDS, hepatitis, STIs and TB), psychiatric problems, inadequate and unhealthy living conditions (incl. nutrition), overcrowding of prisons. These are addressed adequately in order to meet the international requirements of equivalence of health care. The scope of this volume is at the same type specific and diverse enough to cover the interests of a large audience that includes many types of practitioners involved in health-related issues in the field of prison health care, such as psychologists, nurses and prison administration officers responsible for health care, legal professionals and social workers.
Keywords: Social sciences.; Forensic medicine.; Health promotion.; Sociology.; elektronické knihy; electronic books